The Duty of Clarity: A Persuasion Effort. Continuity and Physics from Boltzmann to Wittgenstein. (20th May 2015) - Montibeller, Marcello
Abstract: Despite several scholars referring to the relationships between the philosophy of Boltzmann and Wittgenstein, this topic is still to be explored. The aim of this paper is to analyse the similarities between their views on mathematical continuum and on the meaning of physical theories and phenomenological states of affairs. In several arguments, they both aim to achieve a similar task: by clarifying the meaning of theories in their concrete use, both authors persuade the reader to abandon an apparently intuitive way of thinking in order to overcome theoretical problems by dissolving them.